Single-cell RNA sequencing of aging neural progenitors reveals loss of excitatory neuron potential and a population with transcriptional immune response - Fritze, Jonas; Lang, Stefan; Sommarin, Mikael; Soneji, Shamit; Ahlenius, Henrik (Frontiers in Neuroscience, 2024)
In the adult murine brain, neural stem cells (NSCs) reside in two main niches, the dentate gyrus (DG), and the subventricular zone (SVZ). In the DG, NSCs give rise to intermediate progenitors (IPs) that differentiate into excitatory neurons, while progenitors in the SVZ migrate to the olfactory bulb (OB) where they mainly differentiate into inhibitory interneurons.Neurogenesis, the production of new neurons, persists throughout life but decrease dramatically during aging, concomitantly with increased inflammation. Many cell types, including microglia, undergo dramatic transcriptional changes but few such changes have been detected in neural progenitors. Furthermore, transcriptional profiles in progenitors from different neurogenic regions have not been compared at single cell level, and little is known about how they are affected by agerelated inflammation.We have generated a single cell RNA sequencing dataset enriched for IPs, which revealed that most aged neural progenitors only acquire minor transcriptional changes. However, progenitors set to become excitatory neurons decrease faster than others. In addition, a population in the aged SVZ, not detected in the OB, acquired major transcriptional activation related to immune responses. This suggests that differences in age related neurogenic decline between regions is not due to tissue differences but rather cell type specific intrinsic transcriptional programs, and that subset of neuroblasts in the SVZ react strongly to age related inflammatory cues.